Crystal structure of tetraaqua[2-(pyridin-2-yl)-1H-imidazole-κ2N2, N3]iron(II) sulfate. (April 2015) - Setifi, Zouaoui; Setifi, Fatima; Francuski, Bojana M.; Novakovic, Sladjana B.; Merazig, Hocine
No abstract available